The Plasmodium falciparum homolog of Vps16 interacts with the core members of the Vps-C tethering complex - Florian Lauruol; Thomas Galaup; Alexandra Bourgeois; Audrey Sergerie; Dave Richard (mSphere)
ABSTRACT The organelles of the apical complex (rhoptries, micronemes, and dense granules) are critical for erythrocyte invasion by the malaria parasite Plasmodium falciparum. Though they have essential roles in the parasite lifecycle, the mechanisms behind their biogenesis are still poorly defined. The Class C Vps proteins Vps11, Vps16, Vps18, and Vps33 constitute the core of the CORVET and HOPS complexes implicated in vesicle tethering and fusion in the eukaryotic endolysosomal system. Work in the model apicomplexan Toxoplasma gondii has revealed that TgVps11 is essential for the generation of the apical complex. P. falciparum possesses all four subunits of the Vps-C complex, and recent work has shown that some of its components were critical for host-cell cytosol trafficking and the biogenesis of the apical complex. We here show that the P. falciparum ortholog of Vps16, a member of the Vps-C complex, is expressed throughout the asexual erythrocytic cycle and that it is potentially associated with the Golgi apparatus and the rhoptries in schizont stage parasites. We then demonstrate by immunoprecipitation and mass spectrometry that PfVps16 interacts with all the members of the canonical Vps-C complex along with the Vps3 CORVET component. Interestingly, three uncharacterized Plasmodium-specific proteins are also found as interactors of PfVps16, and structural predictions revealed that two of them possess folds commonly found in proteins present in membrane tethering complexes. These findings suggest that P. falciparum may possess both conserved and parasite-specific features within its endosomal tethering machinery.IMPORTANCEThe malaria parasite relies on special compartments to invade red blood cells. These are key to the parasite’s ability to infect, but how these are generated is not well known. In eukaryotic cells, certain protein assemblies, called tethering complexes, help move and fuse small transport vesicles, which is important for building and maintaining organelles. Plasmodium falciparum possesses some of these proteins, and recent studies suggest they play an important role in building its infection machinery and transporting material inside the parasite. We found that the malaria parasite possesses additional components associated with the typical tethering proteins and that these are not found in other eukaryotes. These results suggest that P. falciparum uses both common and unique tools to create the cellular machinery it needs to infect red blood cells. We propose that the Plasmodium-specific components might represent interesting targets for the development of antimalarials with potentially reduced side effects since they are not present in humans.